Penetrating Trauma : A Practical Guide on Operative Technique and Peri-Operative Management - Velmahos, George C.; Degiannis, Elias; Doll, Dietrich (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides clear practical guidance on all aspects of the surgical treatment of penetrating trauma and aims to foster the type of strategic thinking that can save patients' lives. The coverage encompasses prehospital care, penetrating injuries to various body regions and specific organs, orthopedic injuries, peripheral arterial injuries, injuries to special groups of patients, including children and the elderly, military injuries, and a range of other topics. Based on their extensive personal experience, expert authors provide step-by-step instructions on evaluation, surgical techniques, and management of perioperative problems. Tips and tricks and technical pearls are highlighted and each chapter includes a list of the most important points to observe. This second edition of Penetrating Trauma has been extensively revised and updated - with inclusion of some entirely new chapters - to take into account the most recent trends in resuscitation, diagnostics, and treatment. It will be an ideal resource for those looking for practical solutions on how to treat injuries surgically.
Keywords: Medicine.; Emergency medicine.; Critical care medicine.; Surgery.; Plastic surgery.; Traumatology.; elektronické knihy; electronic books